Gender bias in the evaluation of New Age music - Colley, A.; North, Adrian; Hargreaves, David (Wiley-Blackwell Publishing Ltd., 2003)
Eminent composers in Western European art music continue to be predominantly male and eminence in contemporary pop music is similarly male dominated. One contributing factor may be the continuing under-valuation of women's music. Possible anti-female bias in a contemporary genre was investigated using the Goldberg paradigm to elicit judgments of New Age compositions. Since stronger stereotyping effects occur when information provided about individuals is sparse, fictitious male and female composers were presented either by name only or by name with a brief biography. Evidence for anti-female bias was found in the name-only condition and was stronger when liking for the music was controlled. Other findings were the tendency for females to give higher ratings, and the association of gender differences in liking of the music with ratings of quality in the name-only condition. These results are relevant to the design of formal assessment procedures for musical composition.